Despolarização Processual nas Ações Individuais de Responsabilidade Civil Sob a Égide da Lei Nº 12.965/2014, o Marco Civil da Internet - Ferreira, Thiago de Freitas (2024)
With the advent of law no. 12.965, of 2014, the Marco Civil da Internet in Brazil, service providers began to be subject to a new civil liability regime for damages resulting from content generated by third parties. The law, however, did not provide clear and specific provisions regarding the actions to be taken to postulate the new rights it aims to protect. Furthermore, the identity of the author of the content from which the alleged damage results is not only uncertain for the victim, but the victim's right to privacy is now constitutionally guaranteed (EC no. 115, of 2022). The present dissertation aims to investigate how the flexibility of Individual Civil Liability Actions in the Brazilian Internet Civil Framework, from the perspective of its subjective conformation, can contribute to the provision of more adequate and efficient judicial protection. The investigation is justified, since, with topics such as hate speech, cancel culture and freedom of expression on social networks being on the agenda of the day, for the purpose of proposing the demand, the victim ends up including the defendant in the action in the common grave. reparatory legitimate subjects (service providers, content providers and anonymous user causing the damage) whose interests are not necessarily and/or entirely convergent and harmonious with each other. In this way, the qualitative research that is intended to be developed, based on a broad doctrinal, legislative and jurisprudential review on the subject, and which is absolutely relevant to the line of research on justice systems, constitutionality and protection of individual and collective rights of this Master's Program in Procedural Law, presents as a working hypothesis that an interpolar migration or even a depolarized action on the part of access and content providers in the Actions of Individual Civil Liability in the Internet Civil Framework.